2018
DOI: 10.1002/cam4.1799
|View full text |Cite
|
Sign up to set email alerts
|

Use of bevacizumab as a single agent or in adjunct with traditional chemotherapy regimens in children with unresectable or progressive low‐grade glioma

Abstract: In pediatric low‐grade gliomas not amenable to complete resection, various chemotherapy regimens are the mainstream of treatment. An excellent overall survival of these patients makes justification of the intensification of chemotherapy difficult and calls for the development of new strategies. Bevacizumab, a humanized monoclonal antibody directed against Vascular endothelial growth factor (VEGF), has been successfully used in combination with irinotecan in a number of adult and pediatric studies and reports. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 51 publications
0
44
1
Order By: Relevance
“…No research has been done on the use of bevacizumab in ACP patients, but one small case series reviewed the use of bevacizumab in three patients with pilocytic astrocytoma (PA), another predominantly cystic tumor, and found that all three patients tolerated the therapy well and resulted in a decrease cyst volumes (22). Bevacizumab has also been shown recently to have clinical and radiographic effects in adult PA patients (23, 24) and has been shown to be a safe and tolerated therapy in pediatric patients with PA and other forms of low-grade glioma (25, 26). Overall, the patients presented tolerated therapy well without significant side effects or complications other than isolated Grade 3 neutropenia without associated infections.…”
Section: Discussionmentioning
confidence: 99%
“…No research has been done on the use of bevacizumab in ACP patients, but one small case series reviewed the use of bevacizumab in three patients with pilocytic astrocytoma (PA), another predominantly cystic tumor, and found that all three patients tolerated the therapy well and resulted in a decrease cyst volumes (22). Bevacizumab has also been shown recently to have clinical and radiographic effects in adult PA patients (23, 24) and has been shown to be a safe and tolerated therapy in pediatric patients with PA and other forms of low-grade glioma (25, 26). Overall, the patients presented tolerated therapy well without significant side effects or complications other than isolated Grade 3 neutropenia without associated infections.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, bevacizumab as a single agent reduces tumor volume and apparent diffusion coefficient [ 16 , 56 , 57 ], and improves field of vision, cranial neuropathy, strength, and gait without tumor progression in some cases [ 58 ]. The combination of bevacizumab with conventional chemotherapy is well tolerated and more effective in preserving vision and improving mobility in patients with inoperable or progressive low-grade glioma [ 59 ]. It also helps to preserve vision in patients with optic pathway gliomas in combination with carboplatin or proton-beam radiation [ 60 ].…”
Section: Antiangiogenics and Brain Tumorsmentioning
confidence: 99%
“…Bevacizumab A humanised monoclonal antibody directed against VEGF, this inhibition leads to a reduction in microvascular growth of tumour blood vessels and thus limits the blood supply to tumour tissues. There are several reports of the benefit of anti-VEGF drugs in uncontrolled case series [35][36][37][38].…”
Section: Mek162 (Binimetinib) Orally Available Inhibitor Of Mapk2 Anmentioning
confidence: 99%